DETERMINATION OF EDUCATIONAL STRESS STATUS OF NURSING STUDENTS AFTER KAHRAMANMARAŞ EARTHQUAKE: A CASE STUDY FROM KİLİS PROVINCE - ATSAL KILIÇ, Büşra; ERKAL İLHAN, Sibel (Göbeklitepe Medical Science Journal, 2025)
This study was conducted to determine the educational stress status of nursing students after the earthquake. Ethics committee approval, institutional and scale usage permissions, as well as informed consent from the participants, were obtained for the study. Data were collected using the Descriptive Characteristics and Earthquake Information Form and the Nursing Education Stress Scale (HESÖ). The research data were evaluated using the SPSS 25.0 program using descriptive statistics such as number, percentage, mean and min-max, normality tests, variance analysis and independent sample t-test for data showing normal distribution, and Mann Whitney U test for data not showing normal distribution. The average age of the 240 nursing students, who were second, third and fourth graders, who participated in the study was 21.80±1.41 (19-28), 70.8% were female and 95.8% resided in earthquake zone provinces during the earthquake.The total and sub-dimension score averages of female students, students aged 23 and over, students who were anxious about starting face-to-face education after the earthquake and students who did not trust the school building after the earthquake were found to be statistically significant (p<0.05). As a result, the most stressful situations for nursing students were determined to be preparing for and taking exams, watching a patient in pain, having to study after working all day, and the fear of making a mistake while caring for a patient. More comprehensive research needs to be done on this subject.